Cases in leadership - Rowe, W.Glenn. (Thousand Oaks, Calif. SAGE Publications, 2013)
Cases in Leadership, Third Edition is a unique collection of 32 real-world leadership cases from Ivey Publishing plus 16 practitioner readings from the Ivey Business Journal. The updated casebook helps business students gain a better understanding of leadership and enables them to be more effective leaders through their careers. Each of the selected cases are about complex leadership issues that require the attention of the decision maker.
Includes bibliographical references
Keywords: Leadership -Case studies